IMPLEMENTASI PROGRAM GERDU KEMPLING BIDANG EKONOMI KOTA SEMARANG TAHUN 2011 - Rani Nur Liutami; Rr Nur Hermini; Reni Windiani (Journal of Politic and Government Studies, 2013)
Poverty is a complex issue, requiring an integrated sustainable and management. Therefore, thegovernment of Semarang city innovated to handling poverty through programs called Gerakan TerpaduBidang Kesehatan, Ekonomi, Pendidikan, Infrastruktur, dan Lingkungan and also called GerduKempling. Poverty is a complex issue, requiring an integrated sustainable and management. Therefore,the government of Semarang city innovated to handling poverty through programs called GerakanTerpadu Bidang Kesehatan, Ekonomi, Pendidikan, Infrastruktur, dan Lingkungan and also called GerduKempling who invited many stakeholder. Every stakeholder who involved has their job each other. In thisresearch is discussing about implementation Gerdu Kempling program in sector economy on 2011 whichis focusing in Tanjung Mas village chief, Mangkang Kulon village chief and Teroboyo Kulon villagechief. The result show that realization Gerdu Kempling program in sector economy is different in eachregion and already going to good governance concept. Apart from that also found the hardest part orhindrance factor in process implementation program.